Avaliação da coordenação das redes de atenção à saúde pela atenção primária no município de São Luiz Gonzaga - Rio Grande do Sul - Basso, Natasha (2023)
The general objective of this study is to evaluate the capacity of Primary Health Care to coordinate the Health Care Networks in the Municipality of São Luiz Gonzaga in the State of Rio Grande do Sul and. A cross-sectional study was developed with professionals who work in primary health care in the city of São Luiz Gonzaga from October 2022 to January 2022. The Instrument for Evaluation of Coordination of Health Care Networks by Primary Health Care was used and analyzed by inferential statistics. Data analysis identified that of the 55 professionals who participated in the study, 83.6% (46) declared themselves female and 65.5% (41.8) were ACS. The average age was 41.51 years and the time of performance was 07 years. The stage of development of the capacity of Primary Health Care to coordinate the Health Care Networks in the city was evaluated as a good condition (81.3%), with the scores being 78.18% for the Population dimension, 90.91 % for APS, 83.64% for Support System, 78.18% for Logistic System and 75.55% for the Governance System dimension. Therefore, even with the satisfactory results, there are weaknesses in the PHC in coordinating the RAS.